ANALISIS RESIKO BAHAYA LIMBAH B3 MENGGUNAKAN METODE HIRARC PADA INSTALASI PEMBUANGAN AIR LIMBAH - Rio Ferdiand Saputra; Andung Jati Nugroho (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2024)
Balai PIALAM, namely the Technical Implementation Unit (UPT) of the PUP-ESDM Office of the DIY Regional Government, is a centralized wastewater treatment plant. The problems that exist in Balai PIALAM are temporary storage of B3 waste does not meet the criteria, leaking storage, excessive capacity, methods that can be used to overcome B3 waste are using the HIRARC method, based on 9 activities of the B3 waste management process. Impact of hazard risk with research results Risk level: Medium 4 hazard effect 6.33%, High2 hazard effect 2.11%, extreme1 hazard effect 1.6%. The stages of making HIRARC are: decomposing the work into steps from the beginning to the end of the process, identifying the source of danger, determining the hazard posed by means of interviews, observations, observations, brainstorming, determining the impact on environmental workers, assessing the likelihood of occurrence is used to determine risk rating. Testing period January 2024, t BOD Input (min 99 mg/L,max 458 mg/L), Output (min 10 mg/L,max 59 mg/L), Average (input 206 mg/L, output 30 mg/L), testing period February 2024, testing t BOD Input (min 84 mg/L, max 288 mg/L), Output (min 12 mg/L, max 43 mg/L), Average (input 154 mg/L, output 24 mg/L). Use of APD such as laboratory coats, masks, special gloves, safety shoes, protective helmets and life vests, face shields. As well as implementing SOP. Control of hazards or risks both in laboratory and operational testing activities using APD: gloves, laboratory coats, safety shoes, protective glasses, masks, life vests, and special vests according to the work done and affirmation of SOP.